Assessing the evolution of oases in arid regions by reconstructing their historic spatio-temporal distribution: a case study of the Heihe River Basin, China - XIE, Yaowen; WANG, Guisheng; WANG, Xueqiang; FAN, Peilei (Frontiers of earth science, 2017)
Oasis evolution, one of the most obvious surface processes in arid regions, affects various aspects of the regional environment, such as hydrological processes, ecological conditions, and microclimates. In this paper, the historical spatio-temporal evolution of the cultivated oases in the Heihe River Basin, the second largest inland watershed in the northwest of China, was assessed using multidisciplinary methods and data from multiple sources, including historical literature, ancient sites, maps and remotely sensed images. The findings show that cultivated oases were first developed on a large scale during the Han Dynasty (121 BC-220) and then gradually decreased in extent from the Six Dynasties period (220-581) to the Sui-Tang period (581-907), reaching a minimum in the Song-Yuan period (960-1368). An abrupt revival occurred during the Ming Dynasty (1368-1644) and continued through the Qing Dynasty (1644-1911), and during the period of the Republic of China (1912-1949), oasis development reached its greatest peak of the entire historical period. The oasis areas during seven major historical periods, i.e., Han, Six Dynasties, Sui-Tang, Song-Yuan, Ming, Qing, and Republic of China, are estimated to have been 1703 km 2, 1115 km 2, 629 km 2, 614 km 2, 964 km 2, 1205 km 2, and 1917 km 2, respectively. The spatial distribution generally exhibited a continuous sprawl process, with the center of the oases moving gradually from the downstream region to the middle and even upstream regions. The oases along the main river remained stable during most periods, whereas those close to the terminal reaches were subject to frequent variations and even abandonment. Socio-economic factors were the main forces driving the evolution of cultivated oases in the area; among them, political and societal stability, national defense, agricultural policy, population, and technological progress were the most important.